2022
DOI: 10.1590/1807-3107bor-2022.vol36.0014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oral leukoplakia with CO2 laser (10,600 nm): analysis of 37 cases

Abstract: Camilla Vieira ESTEVES (a) Camila de Barros GALLO (a) Carina DOMANESCHI (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Different definitions for recurrence may result in different rates reported in the literature. [ 31 32 33 ] Similar results are shown in studies by Yang et al , and Monteiro et al , some patients treated with laser can recur. Chiesa et al ., concluded in their study that the age of the operated patients and the size of resected lesions are significantly predictive for the development of relapses and new leucoplakia.…”
Section: Discussionsupporting
confidence: 82%
“…Different definitions for recurrence may result in different rates reported in the literature. [ 31 32 33 ] Similar results are shown in studies by Yang et al , and Monteiro et al , some patients treated with laser can recur. Chiesa et al ., concluded in their study that the age of the operated patients and the size of resected lesions are significantly predictive for the development of relapses and new leucoplakia.…”
Section: Discussionsupporting
confidence: 82%
“…25 A research study also identified small bone necrosis at a rate of 8%, delayed wound healing at a rate of 4%, and sclerotic scars at a rate of 4%. 21  Lesion resolution rates were reported in 43.2% 20 and 47.4% 18 of the patients. The disease-free survival rate during the first year was 52.9% in a study.…”
Section: Results Of Individual Studies Oral Potentially Malignant Dis...mentioning
confidence: 92%
“…Oral tumors and OPMDs were found in three studies. [24][25][26] Some studies showed no postoperative complications 20,42,43 ,and one study found no complication in 64.1% of the patients, 18 whereas others claimed the following complications:  Postoperative pain: In a research study, 23 the numerical rating scale (NRS) score declined considerably from 1 month to 1 year. In additional trials, visual analog scale (VAS) ratings varied from 2 to 4, 44 0 after 7 days, 25 1.8 on the first day before declining to 0.03 on day 7, 26 and 6 in 10.4% of the patients.…”
Section: Results Of Individual Studies Oral Potentially Malignant Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studied have reported good post-operative healing with no complications in case of laser resection of leukoplakia. [2][3][4][5][6] Wladimir Gushiken de 7 in their reported analysis of 37 cases of laser excision of leukoplakia, reported that in 13/37 patients, leukoplakia recurred; and 8/37 patients, a malignant transformation occurred. Frame et al have reasoned that the new epithelium formed after laser application which migrates from the periphery to cover the wound may originate from an area of potentially unstable mucosa thereby explaining the recurrence.…”
Section: Discussionmentioning
confidence: 99%